The Development of New Electronic Percussion Instruments in Popular Music of the 1980s: A Technical Study - Michael, Carlucci (Université d'Ottawa / University of Ottawa, 2014)
The influence of electronic percussion (in particular, the Simmons Drum Company’s innovations) on the compositions and evolution of 1980s Pop music can be examined through technological advancements as well as stylistic characteristics of drum partitions of the decade. Archived company catalogues in collaboration with Matt Dean’s historical timeline provide a clear understanding of the advancements during the time of the company’s tenure at the top of the electronic percussion industry. Definitions of the terms “style” and “genre” in both the primary and secondary approaches -by Allan Moore and other theorists- are used. The stylistic properties which create a genre are key in understanding the political, social, and cultural effects on the music. Ultimately, stylistic traits provide sufficient evidence in order to examine similar compositions which were sub-categorized differently on Billboard’s hit charts. Dave Carlton’s Hook Theory is a major resource in selecting pieces of music which share similarities. The differences in sub-categorization identified in this study are shown to derive from the transition to and the use of electronic percussion.
Keywords: Pop Music; Electronic Percussion; History; Acoustic Percussion